A boundary reconstruction scheme for lattice Boltzmann flow simulation in porous media. (5th May 2009) - Suga, K.; Tanaka, T.; Nishio, Y.; Murata, M.
A novel boundary reconstruction scheme is developed utilising the reinitialisation scheme of the Level Set Method (LSM). The proposed scheme transfers usual digitally defined step-like boundary data to continuously smooth surface data. It is confirmed that the lattice boltzmann simulation by the Interpolated Bounce-Back (IBB) Boundary Condition (BC) with the present scheme well reproduces the drag coefficients of a cylinder and a sphere. Then this numerical scheme is applied to simulate flows in porous media which have the body-centred cubic structure. The results indicate that the present scheme improves the shape representation and thus the prediction accuracy is less sensitive to grid resolutions.